2002
DOI: 10.1016/s0035-9203(02)90424-4
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Helicobacter pylori infection in Guadeloupe

Abstract: 854 sera collected from blood donors in Guadeloupe were screened for Helicobacter pylori immunoglobulin G antibodies by a commercial enzyme-linked immunosorbent assay kit. The overall prevalence was 55.2%; it increased significantly with age from 36.1% at 18-19 years to 63.7% at 50-59 years (P = 0.003).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…There was no significant difference in the overall prevalence of H. pylori infection between males (53.1%) and females (61.4%), p>0.05. This finding is compatible with other studies (1,10,24,(26)(27)(28). However, some studies have found a higher prevalence of H. pylori infection in males, which may be related to higher exposure of the males to potential environmental sources of infection (29)(30).…”
Section: Discussionsupporting
confidence: 92%
“…There was no significant difference in the overall prevalence of H. pylori infection between males (53.1%) and females (61.4%), p>0.05. This finding is compatible with other studies (1,10,24,(26)(27)(28). However, some studies have found a higher prevalence of H. pylori infection in males, which may be related to higher exposure of the males to potential environmental sources of infection (29)(30).…”
Section: Discussionsupporting
confidence: 92%
“…Although the prevalence of H. pylori antibodies in adults was similar to other studies, 26,27 it was surprising that there was an inverse association between anemia and H. pylori seroreactivity. This finding contrasts with previous studies that have reported a positive association.…”
Section: Discussionsupporting
confidence: 83%
“…In the French West Indies, however, seroprevalence of H. pylori has been shown to increase with age, with prevalence rate exceeding 55% of blood donors (Weill et al, 2002). Prevalence was lower to that reported for other Caribbean countries (Edwards et al, 1997;Lindo et al, 1999) that have a higher incidence of stomach cancer than Martinique.…”
Section: Discussionmentioning
confidence: 75%